Development of geographical weightage regression model for urban crime in Sungai Petani, Kedah, Malaysia - Mansor, Nur Suhaili (2019)
Development and urbanization may bring prosperity to some urban dwellers, but most often, socio-economic imbalances do take place that condemned the low-income group to poverty. It is noted that the changes in land use do bring about changes in the urban formation that leads to changes in the daily life activities of the people, but social imbalances do create new opportunities or change the existing opportunities for them to commit crimes. This research discussed the subject matter of land use and its relation to the neighbourhood perception of safety on criminal activity located in Sungai Petani, Kedah. The study firstly used SPOT-5 satellite images to measure urban growth for thirteen years from 2000 to 2013 processed by ERDAS IMAGINE software. The first objective is on urban changes from the year 2000 to 2013 is recorded at 24.2% growth. Then, secondly, the crime data that combined three types of crime, including violent crime, property crime, and drug offenses were collected from the Police Department in Sungai Petani. The crime distribution hotspot in the town of Sungai Petani was identified, and the direction of urbanization taking place was observed to be taking place towards the industrial sites of Kulim, Kedah and Pulau Pinang. Thirdly, in addition to these data, neighbourhood perception of safety data was obtained from 444 respondents through a questionnaire that measured several variables, viz., urban security, individual safety, social problems, crimes, development, and governance of the locality studied were interviewed and analyzed. Analytical Hierarchy Process (AHP) analysis was used to examine the suitable variable to be included in the model developed. The result revealed that land use is perceived to influence crime relative to the neighbourhood perception of safety whereby the weight for land use is 88.7 percent while the weight for perception is only 16.7 percent that includes the issues of governance, social problem, criminal problem, urban security, and individual safety. The aim of this study is also to investigate and to establish an urban crime model. The factors from AHP that produce consistent and realistic weight values of influent factors on criminal activity are residential, commercial and road. Besides the latter, neighbourhood perception of safety is influenced by the factors of gangs, burglary, fear of crime and fear of neighbourhood crime.